A molecular study regarding the spread of vanA vancomycin-resistant Enterococcus faecium in a tertiary hospital in China. (December 2022) - Liu, Sha; Li, Yan; He, Ziqiang; Wang, Yan; Wang, Jing; Jin, Dong
ABSTRACT: Objectives: Vancomycin-resistant enterococci (VRE) are one of the most important bacterial causes of healthcare-associated infections (HAIs). In China, the detection rate of VRE Enterococcus faecium (VREfm) is low, although VREfm had a high prevalence in our hospitals between 2013–2015. In this study, we used molecular typing methods combined with epidemiological data to investigate the spread of VREfm in our hospital. Methods: The characteristics of E. faecium strains isolated from 89 patients with HAIs, including antibiotic susceptibility and virulence genes, were analyzed. This study analyzed 50 E. faecium strains isolated from 47 intensive care unit and Emergency ward patients using core genome Multilocus Sequence Typing and transposon typing. Epidemiological information about those patients was also analyzed. Results: Twenty-seven E. faecium isolates containing the vanA gene were identified as VREfm in 89 non-duplicate E. faecium isolates. The major clonal VREfm strains that persisted from 2013–2015 were CT1/ST78/PFGE cluster A that contained transposon type Ⅰ. The other CT4/ST363/PFGE cluster of VREfm strains also contained transposon type Ⅰ. Three patients acquired different clonal E. faecium strains during the hospital period, and the VREfm strain infected one patient. Conclusions: In this study, we report the spread caused by vanA vancomycin-resistant E. faecium strains of different cluster types with the same type of transposon in a tertiary hospital. Our literature review revealed that this is the first report of the HAIs caused by ST363/CT4 VREfm strains.